Anxious men : masculinity in American fiction of the mid-twentieth century - Baldwin, Clive (Clive David) (Edinburgh University Press, 2020)
Focusing on a complex and contentious period that was formative in shaping American society and culture in the twentieth century, this book sheds new light on the ways in which fiction engaged with contemporary notions of masculinity.